2017
DOI: 10.1038/s41598-017-15062-9
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide linkage and association study implicates the 10q26 region as a major genetic contributor to primary nonsyndromic vesicoureteric reflux

Abstract: Vesicoureteric reflux (VUR) is the commonest urological anomaly in children. Despite treatment improvements, associated renal lesions – congenital dysplasia, acquired scarring or both – are a common cause of childhood hypertension and renal failure. Primary VUR is familial, with transmission rate and sibling risk both approaching 50%, and appears highly genetically heterogeneous. It is often associated with other developmental anomalies of the urinary tract, emphasising its etiology as a disorder of urogenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…9 Segregation analyses and linkage studies suggested the contribution of rare variants with large effects and multiple modes of inheritance. [12][13][14][15][16][17][18][19] Urinary tract formation in the mouse begins at E9, when nephric ducts form and extend, joining the cloaca. Cloacal septation separates the hindgut from the urogenital sinus (UGS) between E11 and E14.…”
mentioning
confidence: 99%
“…9 Segregation analyses and linkage studies suggested the contribution of rare variants with large effects and multiple modes of inheritance. [12][13][14][15][16][17][18][19] Urinary tract formation in the mouse begins at E9, when nephric ducts form and extend, joining the cloaca. Cloacal septation separates the hindgut from the urogenital sinus (UGS) between E11 and E14.…”
mentioning
confidence: 99%
“…While VUR remains a common pediatric disorder, the ability for clinicians to determine who will develop recurrent urinary tract infections, who will develop renal scarring, and how these patients should be managed remains unclear. An additional challenge is the fact that VUR is both genetically 30,31,32,33,34 and phenotypically heterogeneous. The purpose of this paper was to ascertain if VUR with joint hypermobility is a common phenotype and to determine if children with VUR and joint hypermobility might be at higher risk for recurrent urinary tract infections and/or renal scars.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may become more widely adopted, especially by families who already have a child with a genetically defined urinary tract malformation, and even more so if specific treatments were to become available. Although these are rare diseases, commoner urinary tract anomalies may have genetic causes, including non-syndromic primary vesicoureteric reflux [28].…”
Section: Clinical Impact Of Urinary Tract Malformationsmentioning
confidence: 99%